2004
DOI: 10.1023/b:pham.0000032999.31948.2e
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Delivery of the Synthetic Cannabinoid WIN 55,212-2: In Vitro/in Vivo Correlation

Abstract: The topical drug treatments provided significant steady-state plasma drug levels for 48 h. The observed in vivo results from the Hill Top Chambers and TTS patches in the guinea pigs were in good agreement with the predicted plasma concentrations from the in vitro data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Mean±SEM pounds. Towards this end, we reasoned that our compounds concurred with other cannabinoid agonists/antagonists such as WIN55,212-2 or rimonabant (SR141716A) (Valiveti et al 2004; Barna et al 2009) in that their absorption might be rapid and complete washout be achieved within 24 h. This assumption guided our time point selection for tissue harvesting. A second consideration pertained to the selection of vehicle for the highly lipophilic cannabinoids.…”
Section: Discussionmentioning
confidence: 91%
“…Mean±SEM pounds. Towards this end, we reasoned that our compounds concurred with other cannabinoid agonists/antagonists such as WIN55,212-2 or rimonabant (SR141716A) (Valiveti et al 2004; Barna et al 2009) in that their absorption might be rapid and complete washout be achieved within 24 h. This assumption guided our time point selection for tissue harvesting. A second consideration pertained to the selection of vehicle for the highly lipophilic cannabinoids.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies have demonstrated that the WIN55, 212-2 induced mild hypothermia and improved the outcome of cardiopulmonary resuscitation (CPR) in a rat model of cardiac arrest (9). The cooling effect of WIN55, 212-2 was rapid and long lasting due to its short mean distribution half-life (0.12 hr) and long mean terminal elimination half-life (4.93 hr) (10).…”
mentioning
confidence: 99%
“…Hence, in vitro studies across EVA copolymer membrane-PSA were completed. Literature reports have shown that EVA membrane (CoTran 9715, 19% w/w of vinyl acetate content) (14,22) laminated with PSA provides very high drug flux rates, as compared to other membrane choices. Hence, in the present study CoTran 9715 laminated with PSA was chosen as a membrane for the fabrication of the patches, where the drug solution was sandwiched between this membrane and the backing membrane.…”
Section: In Vitro Permeability Studies Across Eva Copolymer Membrane-psamentioning
confidence: 99%